Unequal : a story of America - Dyson, Michael Eric; Favreau, Marc, 1968- (Little, Brown and Company, 2022)
A collection of stories of American civil rights leaders past and present--from Mary Church Terrell fighting against segregation and Ida B. Wells and her exposé against lynching, to the Black Lives Matter movement and Nikole Hannah-Jones's "1619 Project."